Polyvinyl pyrrolidone-assisted synthesis of crystalline manganese vanadate microtubes - Li-Zhai Pei; Yin-Qiang Pei; Yi-Kang Xie; Chang-Zhou Yuan; Dian-Kai Li; Qian-Feng Zhang (Materials Research, 2013)
Manganese vanadate microtubes have been synthesized by a facile polyvinyl pyrrolidone-assisted hydrothermal route. X-ray diffraction pattern confirms that the microtubes are composed of monoclinic MnV2O6, tetragonal V2O5 and orthorhombic MnO2 phases. The outer diameter and inner diameter of the microtubes are about 300 nm-3 µm and 200 nm-1 µm, respectively. The tube wall thickness of the microtubes is about 50 nm-1 µm. The possible formation process of the manganese vanadate microtubes has been proposed as a polyvinyl pyrrolidone-assisted growth mechanism.